2021
DOI: 10.3390/plants10071274
|View full text |Cite
|
Sign up to set email alerts
|

Primary Root and Mesocotyl Elongation in Maize Seedlings: Two Organs with Antagonistic Growth below the Soil Surface

Abstract: Maize illustrates one of the most complex cases of embryogenesis in higher plants that results in the development of early embryo with distinctive organs such as the mesocotyl, seminal and primary roots, coleoptile, and plumule. After seed germination, the elongation of root and mesocotyl follows opposite directions in response to specific tropisms (positive and negative gravitropism and hydrotropism). Tropisms represent the differential growth of an organ directed toward several stimuli. Although the life cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 180 publications
0
16
0
Order By: Relevance
“…Likewise, the study allowed the observation of a positive correspondence between the two principal components (PC1 and PC2) and the GCA of the parents; that is, with a higher GCA of the parents in F 1 and F 2 , the association of the parents regarding the two principal components (PC1 and PC2) was higher and is similar to those obtained by other studies, where positive correlations were observed with the 1197AM (Pionner) corn in the field, OH, USA, for grain weight when a depth of 51 and 76 mm was established [52]. Therefore, the adjustments in the depth of sowing can improve the PCA of some genotypes, although the responses of grain yield can differ according to the soil type [56], as is the case of H-48, HS-2 and Promesa, ST34, ST11 and ST112 of Chalqueño race [57], IBM Syn10, B73, Mo17 [58], US13, Hopi, Navajo [59] and P11974M [47], which show a different response to the depth of sowing and soil, where the GCA of the LM-LC of some genotypes were associated with the speed and percentage of emergence and these were associated successively with the two principal components (PC1 and PC2) in the agricultural practice known as deep sowing, which is still used in semi-arid regions of Mexico [60] and in southwest USA [13]. Therefore, the parents (H-48, HS-2 and Promesa) with a higher GCA in LM-LC presented a greater relation with the two principal components, which suggests that LM-LC could be a response trait to stress from deep sowing [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the study allowed the observation of a positive correspondence between the two principal components (PC1 and PC2) and the GCA of the parents; that is, with a higher GCA of the parents in F 1 and F 2 , the association of the parents regarding the two principal components (PC1 and PC2) was higher and is similar to those obtained by other studies, where positive correlations were observed with the 1197AM (Pionner) corn in the field, OH, USA, for grain weight when a depth of 51 and 76 mm was established [52]. Therefore, the adjustments in the depth of sowing can improve the PCA of some genotypes, although the responses of grain yield can differ according to the soil type [56], as is the case of H-48, HS-2 and Promesa, ST34, ST11 and ST112 of Chalqueño race [57], IBM Syn10, B73, Mo17 [58], US13, Hopi, Navajo [59] and P11974M [47], which show a different response to the depth of sowing and soil, where the GCA of the LM-LC of some genotypes were associated with the speed and percentage of emergence and these were associated successively with the two principal components (PC1 and PC2) in the agricultural practice known as deep sowing, which is still used in semi-arid regions of Mexico [60] and in southwest USA [13]. Therefore, the parents (H-48, HS-2 and Promesa) with a higher GCA in LM-LC presented a greater relation with the two principal components, which suggests that LM-LC could be a response trait to stress from deep sowing [13].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the adjustments in the depth of sowing can improve the PCA of some genotypes, although the responses of grain yield can differ according to the soil type [56], as is the case of H-48, HS-2 and Promesa, ST34, ST11 and ST112 of Chalqueño race [57], IBM Syn10, B73, Mo17 [58], US13, Hopi, Navajo [59] and P11974M [47], which show a different response to the depth of sowing and soil, where the GCA of the LM-LC of some genotypes were associated with the speed and percentage of emergence and these were associated successively with the two principal components (PC1 and PC2) in the agricultural practice known as deep sowing, which is still used in semi-arid regions of Mexico [60] and in southwest USA [13]. Therefore, the parents (H-48, HS-2 and Promesa) with a higher GCA in LM-LC presented a greater relation with the two principal components, which suggests that LM-LC could be a response trait to stress from deep sowing [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, soon after the maize seeds germinated in the soil, the elongated MES (an embryonic structure between COL node and basal part of seminal root in seedlings) pushes the COL (a conical structure that sheaths the shoot apex) through the soil surface. At the soil surface, incident light represses MES and COL elongation, induces leaf expansion, and promotes root formation ( Liu et al., 2017 ; Rodríguez and Cassab, 2021 ; Zhao and Zhong, 2021 ). As cells are recruited to the emerging leaf primordia, proplastids differentiate into the dimorphic bundle sheath and mesophyll cell chloroplasts, and the photoautotrophic phase of sporophytic development is initiated ( Markelz et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different crop species have evolved diverse organs to adapt to deep-sowing stressors, including elongated mesocotyl in rice ( Oryza sativa L.) [ 10 ] and elongated coleoptile in wheat ( Triticum aestivum L.) [ 11 ] and barley ( Hordeum vulgare L.) [ 12 ]. These structures help the emergence of the shoot tips and the first internode from the embryo to the soil surface; the co-elongated mesocotyl and coleoptile in maize send the buds to the soil surface [ 13 , 14 ], where natural light represses the continued elongation of mesocotyl and coleoptile and induces leaf expansion [ 7 , 15 ]. However, different crops have different degrees of deep-sowing tolerance due to genetic variations.…”
Section: Introductionmentioning
confidence: 99%